2012
DOI: 10.1007/s00431-012-1735-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of blood pressure, obesity, and adherence to the Mediterranean diet with indices of arterial stiffness in children

Abstract: Obesity and adherence to the Mediterranean diet patterns are factors related independently to indices of AS even in 12-year-old children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 34 publications
7
48
0
1
Order By: Relevance
“…Also, our data coincide with those obtained in the enKID study conducted in the past decade (30.4%) and are very close to those reported for other Mediterranean countries as Portugal (31.5%) and Italy (25.1% -27.6%) [39][40][41]. On the other hand, are lower than the values obtained in Greece (overweight: 30.3% and obese: 13.0%) and higher than those corresponding to Morocco and Tunisia where overweight children are below 10.0% [22,[42][43][44].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Also, our data coincide with those obtained in the enKID study conducted in the past decade (30.4%) and are very close to those reported for other Mediterranean countries as Portugal (31.5%) and Italy (25.1% -27.6%) [39][40][41]. On the other hand, are lower than the values obtained in Greece (overweight: 30.3% and obese: 13.0%) and higher than those corresponding to Morocco and Tunisia where overweight children are below 10.0% [22,[42][43][44].…”
Section: Discussionsupporting
confidence: 82%
“…On the same line, Lydakis et al in a sample of 277 Greek children aged 12 years, observed that the KIDMED score is negatively associated to "augmentation index" in the brachial artery, regardless of BMI [22]. This study was the first to analyze the relationship between MD and arterial stiffness in children, although a previous study had proven that daily consumption of fruits and vegetables (included as items in the KIDMED index) during childhood, was a protective factor for hypertension and arterial stiffness in adults [54].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…employed this methodology, [40][41][42][43][44] and findings from this study support the need to generate reference values relevant to children. The finding that HbA 1c loaded onto the adiposity factor, while FBG loaded onto the vascular factor, is consistent with research identifying that the these two variables reflect different underlying physiological constructs, with FBG reflecting short-term glycemic control 16 and HbA 1c reflecting chronic glycemic control.…”
Section: Comparison With Other Studiessupporting
confidence: 55%
“…There is some controversy regarding the relationship between obesity and MD adherence (30) . Several studies have reported that overweight or obese children and adolescents showed significantly lower levels of MD adherence (20,31,32) . Lydakis et al (31) conducted a cross-sectional study which concluded that overweight and obese children had significantly lower MD adherence levels in comparison to children with a normal BMI.…”
mentioning
confidence: 99%